Achieve the requirements of the Administrative Control according to human resource management practices - القيسي, بلال جاسم; مهلي, حسن فليح (Journal of Economics and Administrative Sciences, 2015)
Human Resources Management Practices (HRMP) and managerial control represent two academic fields that have been and still are the focus of many studies. However, merging both fields and studying the relationship that connects them and also the role that HRMP play in achieving the requirements of managerial control represents a new and novel study according to the available literature in these fields.To achieve these goals, this study has been conducted, using the surveying questionnaire method, on a sample of ten general inspector offices in Iraq that work in the field of control for ministries and independent committees. A questionnaire has been used to collect the data which was analyzed with several statistical measures using the Statistical Package for the Social Sciences (SPSS). A targeted sample of 179 participants has been selected from the general inspector offices with ranks of department manager and unit manager.The study focuses on understanding the role of HRMP in these offices and highlights the areas that need the most attention. The study also proposes solutions to handle and overcome points of weakness and activate the role of managerial control by achieving its needed requirements, Two main hypotheses have been derived, with each branching into secondary hypotheses, to test the connection relation and the effect between variables.              The study has proved the two main hypotheses through  demonstrating the relationship and the effect of the variables in study. The study reaches conclusions on the relationship between the performance appraisal system and the incentive program and also between the performance appraisal system and the training needs assessment. The study presents some recommendations about the activation of HRMP and requirements for achieving managerial control.